2010
DOI: 10.1111/j.1460-9568.2010.07110.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed structural connectivity is related to inattention and impulsivity in adult attention deficit hyperactivity disorder

Abstract: Inattention and impulsivity are the most prominent clinical features of attention deficit hyperactivity disorder (ADHD) in adulthood. Structural and functional neuroimaging studies of subjects with ADHD have demonstrated abnormalities in several brain areas, including fronto-striatal and fronto-cerebellar networks. Mostly, these studies were based on volumetric measurements and have been conducted in children. We investigated white matter (WM) integrity and correlation with measures of attention and impulsivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
166
6
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(192 citation statements)
references
References 44 publications
11
166
6
9
Order By: Relevance
“…One of the most consistent findings from studies of anatomical connectivity, in children and adolescents with ADHD, is reduced fractional anisotropy (Hamilton et al 2008;Makris et al 2008;Luders et al 2009;Konrad et al 2010) of fronto-striatal tracts (within the cortico-striatal network) and fronto-parietal tracts (within the ventral and dorsal attention network). These findings have been supported by some (Dickstein et al 2006;Rubia 2011;Cubillo et al 2012) but not all studies of functional connectivity (Tian et al 2006;Uddin et al 2008).…”
Section: Introductionmentioning
confidence: 89%
“…One of the most consistent findings from studies of anatomical connectivity, in children and adolescents with ADHD, is reduced fractional anisotropy (Hamilton et al 2008;Makris et al 2008;Luders et al 2009;Konrad et al 2010) of fronto-striatal tracts (within the cortico-striatal network) and fronto-parietal tracts (within the ventral and dorsal attention network). These findings have been supported by some (Dickstein et al 2006;Rubia 2011;Cubillo et al 2012) but not all studies of functional connectivity (Tian et al 2006;Uddin et al 2008).…”
Section: Introductionmentioning
confidence: 89%
“…As our a priori hypothesis entailed that τ reflects attentional processes, we based our ROIs on the attentional network model of Makris and colleagues 21 and on previous work by Lin and colleagues 13 and Konrad and colleagues. 28 However, while providing the largest statistical power, our ROI approach did not allow us to formulate novel hypotheses about other regions important for attention and ADHD; whole brain analyses in larger samples will be necessary. Similarly, as we used the diagnostic measure only to link FA values, we might have missed more specific links with quantitative measures of inattention and hyperactivity/impulsivity.…”
Section: Limitationsmentioning
confidence: 99%
“…26,27 Another study showed that task-related measures of attentional performance in adults with ADHD correlated significantly with FA in the right SLF. 28 The ILF connects the occipital with the temporal cortices, 21 and bilateral regions of the ILF are also abnormal in children and adults with ADHD. 27,29 Furthermore, the microstructural integrity of the right CB was found to be altered in adults with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…The other meta-analysis was of whole-brain voxel-based morphometry imaging studies, avoiding the a priori bias of region selection, and identified a significant regional gray matter reduction in ADHD children compared with control subjects in right putamen and globus pallidus (Qui et al 2009;Qiu et al 2010). Diffusion tensor imaging studies have furthermore provided evidence for abnormalities at the neural network level, showing abnormalities in multiple white matter tracts in cingulate and fronto-striatal, as well as fronto-parietal, fronto-cerebellar, and parieto-occipital white matter tracts, in children, as well as adults, with ADHD compared with comparison subjects (Konrad et al 2011;Thomason and Thompson 2011;Konrad et al 2010;Ashtari et al 2005). Longitudinal imaging studies have provided evidence that the structural abnormalities in these latedeveloping fronto-striato-cerebellar and frontoparietal systems are due to a late structural maturation of these regions (Rubia, 2011;Rubia et al 2009;Yang et al 2007).…”
Section: Neurophysiological Substrate Of Intra-individual Variabilitymentioning
confidence: 99%